Proyecto de factibilidad para la implementación de una empresa envasadora y comercializadora de agua purificada en botellones de 20 litros, en la ciudad de Tena, provincia de Napo, para el año 2016 - Andi Intriago, Ruben Antonio (2017)
The objective of this study is to determine the commercial viability of the implementation of a packer and marketer of purified water in bottles of 20 liters, in the city of Tena, Napo province, for the year 2016, that allows to know through technical studies, which are administrative and operating procedures suitable for the local market bottled purified water in bottles of 20 liters that meet the need of the customers, in addition to know if the proposal is acceptable based on the results. For the development of the objectives identified was used the following methodology: the inductive method, which by its feature of observation and study of the facts leads to the generalization of the project, the deductive method which obtain conclusions and results helped to determine the size of the sample of the population, and the statistical method that enabled us to develop the analysis and interpretation of the data obtained; carried out a market study in which basically applied to families in a sample of 370 surveys in the city of Tena and 3 business bidders dedicated to the production and marketing of bottled purified water in bottles of 20 liters, located in the canton Tena, being able to determine that for the first year there is a potential demand of 10,267 consumers, the actual demand is of 8,796 potential customers and the effective demand in units of 315,420; on the supply side we have the amount of 114,018 bottles of purified water of 20 liters, which gives us as a result that there is an unsatisfied demand of 201,402 bottles of purified water. Within the technical study calculated the overall installed capacity of 115,200 bottles of 20 liters of purified water and will be launched with a capacity of 80% with the result that the plant will produce 92,160 for the first year. The firm's location within the city of Tena will be in the area called Barrio San Antonio in the avenida Muyuna; then the engineering of the project where it is proposed that the distribution of the plant, flow charts of the processes of acquisition of materials, production and marketing, as well as the requirement of machinery, materials and human talent needed for the company. In the organizational study the company is constituted as a unipersonal limited liability and how to reason social "PURIFIED WATER ANDI E.U.R.L." The staff consists of: a manager, a legal adviser eventually, a salesperson, an accountant, a dispatcher, a driver and two people of the same production that are set out in the structural organization chart, positional and functional, defining their profiles and responsibilities in the manual of functions of the company. The financial analysis determined that the total investment for this project will be $ 99,560.16 dollars of the United States of America, which will be financed with a 30% of own capital $29,865.05 dollars of the United States of America, and the remaining 70% with a credit in the National Financial Corporation $69,685.11 dollars of the United States of America. The first year costs reflect a value of $ 91,242.47 dollars of the United States of America and the income will reach the $118,615.21 dollars of the United States of America, to obtain a net income of $26,020.24 dollars of the United States of America. In the economic evaluation the results obtained were: THE VAN OF $ 29,335.54 dollars of the United States of America, the IRR of 18.68% higher than the 11.83% interest rate proposed by the National Financial Corporation, the recovery period of the investment is 4 years, 4 month and 11 days and the Beneficio-Costo Relationship is $1.30 dollars of the United States of America, and finally it was determined that the project will support an increase of up to 10.09% of the costs and a decrease of 7.78% of revenues. The assessment of the environmental impact of the project after the uprising with the Leopold matrix, it was determined that the affectations that can exist within the production process of bottles of purified water, are only the noise of the machines produce, it has implemented measures.